Analysis of bile acid in saliva of patients with laryngopharyngeal reflux and non-laryngopharyngeal reflux - Ade Asyari; Refi Amalia Utami; Eti Yerizel; Andani Eka Putra; Firdawati Firdawati (PERHATI-KL, 2023)
ABSTRACT — Background: Laryngopharyngeal reflux (LPR) is the backflow of gastric and or duodenal fluid into the larynx, pharynx, trachea, and bronchi. The prevalence of LPR is difficult to determine due to the limited gold standard and the large variety of LPR symptoms. Damage can occur due to the decrease in pH value and also because of exposure to harmful enzymes in reflux, including bile acid. Purpose : This study was conducted to analyze bile acid levels in the saliva of LPR patient and non LPR subject. Methods: This study is an observational study with a case-control design. The study was conducted in the ORL-HNS Department of Dr. M. Djamil Hospital, Padang, West Sumatra, Indonesia. The total sample size was 44 people. We enrolled 22 healthy subjects as the control group and 22 patients suspected of having LPR. Result: LPR patients are more common in women than in men, with 12 women and 10 men. Bile acid in the LPR group means of is 25.08±7.67µM, meanwhile, in the healthy group, the mean was 18.99±8.26 µM. There is a statistically significant in the incidence of LPR with the bile acids (p = 0.015) based on t- independent test. Conclusion: Our study confirmed that bile acids in saliva play a major role in diagnosing LPR.